Low-Complexity Geometry-Based MIMO Channel Simulation. (1st July 2007) - Kaltenberger Kaltenberger, Florian Florian; Zemen Zemen, Thomas Thomas; Ueberhuber Ueberhuber, Christoph W. Christoph W.
Abstract : The simulation of electromagnetic wave propagation in time-variant wideband multiple-input multiple-output mobile radio channels using a geometry-based channel model (GCM) is computationally expensive. Due to multipath propagation, a large number of complex exponentials must be evaluated and summed up. We present a low-complexity algorithm for the implementation of a GCM on a hardware channel simulator. Our algorithm takes advantage of the limited numerical precision of the channel simulator by using a truncated subspace representation of the channel transfer function based on multidimensional discrete prolate spheroidal (DPS) sequences. The DPS subspace representation offers two advantages. Firstly, only a small subspace dimension is required to achieve the numerical accuracy of the hardware channel simulator. Secondly, the computational complexity of the subspace representation is independent of the number of multipath components (MPCs). Moreover, we present an algorithm for the projection of each MPC onto the DPS subspace in𝒪 ( 1 ) operations. Thus the computational complexity of the DPS subspace algorithm compared to a conventional implementation is reduced by more than one order of magnitude on a hardware channel simulator with 14-bit precision.